Leni Riefenstahl: prophet of media fascism - feitoza, frederico (2012)
There is a Fascist knowledge which flows on the media imagery in a negotiated and politically corrected way. In this paper, I intend to speculate about this knowledge, starting from a set of images which somatize it in an exemplary way. I refer to the book of photographs The Last of Nuba (1972) by the German artist Leni Riefenstahl. I draw attention to the cynical totalitarianism that underlies the process of political correctness in her images. To this end, I start from a symptomatic conception of culture, psychoanalytically and historically engaged, in which the visual signs produced and celebrated by this culture point to a repressed dimension of its subjective dispositions. I will draw special attention to the very composition of the images; to the relation between its formal elements, between what is visible and what has particular signification, between the expectations and satisfactions they engender, and the conflicts between content and expression. The Last of Nuba marks the passage from the opened celebration of fascism to a more subtle and politically appropriate way of expression of this political sensitivity. It precedes the obsessed ideal of a perfect physicality under the reactive guise of a “healthy” multiculturalism as we see it nowadays on the mainstream media. The wider aim of this paper is to deepen our perception of fascist aesthetics.